STATUS GIZI DAN PENGETAHUAN ORANG TUA TENTANG ASUPAN NUTRISI BALITA DITAMAN PENITIPAN ANAK (TPA) PELANGI NUSA - Ratih Kumoro Jati (Universitas Jenderal Achmad Yani Yogyakarta, 2012)
Introduction: National Final Examination (UAN) often gives psychological impacts for students, especially anxiety. If anxiety is allowed to continue, it will give negative impacts on teens, such as a decision to commit promiscuity. Therefore, there are needs for therapies that can reduce the anxiety of students in facing exam, one of which is Emotional Freedom Techniques (EFTs). Objective: To determine the effect of EFT on anxiety in the face of UAN at high school students. Methods: The research method was quasi experimental with pretest-posttest design. Prior to therapy, anxiety screening was performed on 137 students using a questionnaire of Pasco-Hernando Community College (PHCC) Anxiety Test. After that, 28 were taken students as the sample divided into 2 groups (control and intervention), each 14 students. The intervention group received 3 times of EFT therapy sessions. Analysis of data was to determine the effect by using a paired t-test and to know the comparison used independent t-test, with α of 0.05. Results: The initial screening results were as follows: mild to moderate anxiety (58, 4%) and moderate to severe anxiety (0.7%). Test results of paired t-test showed p = 0, 046 (p <0, 05). In addition, based on independent t-test, p was 0.000 (p <0.05); thus, the mean value of anxiety of the intervention group was significantly lower than that of the control group. Conclusion: EFT effectively reduced student anxiety in facing UAN in SMA N 1 Pakem, Sleman, Yogyakarta. It is suggested EFT can be used as a non-pharmacological psychological therapy. Keyword: EFT, anxiety, adolescents